SEAGRASS DISTRIBUTION BASED ON THEIR SEDIMENT CHARACTERISTICS IN PUNTONDO WATERS, TAKALAR DISTRICT, SOUTH SULAWESI, INDONESIA - Syafiuddin; MUH.AQRAM RAMADHAN; La Nafie, Yayu A.; Mashoreng, Supriadi; Lanuru, Mahatma (Hasanuddin University, 2021)
Seagrass distribution is influenced by many factors, including sediment characteristics. This study aims to determine the distribution of seagrass based on their sediment characteristics. Observations and sampling were carried out in the waters of the Puntondo Bay, Takalar Regency. This study observed the cover and density of seagrass species, water depth, water transparency, sediment’s total organic matter and size of sediment grains. There were five species of seagrass found in the area, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halophila ovalis and Syringodium isoetifolium with sediment types of medium sand and coarse sand. Results of the regression analysis showed that the relationship between sediment particle size and seagrass density with the highest coeficient determination (R2=0,3346) was in seagrass Cymodocea rotundata, whereas the lowest was in Syringodium isoetifolium. Keywords: Seagrass, Puntondo, aters, Sediment grain size, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halophila ovalis, Syringodium isoetifolium.